Relationship Among Institutional Quality, Tax Revenue and Economic Growth at Provincial Level: Evidence from Vietnam - Phuong , Lien, Nguyen (Asian Journal of Empirical Research, 2016)
To investigate the relationship among institutional quality, tax revenue, and economic growth in Vietnam, this work applies the Granger test for a panel data of 60 provinces in Vietnam during the period 2006 - 2014. In addition, using the two-step system generalised method of moments estimation supports this study to evaluate the degree of impact of interaction between quality of institutions and tax revenue on economic growth in more detail. The results provide a bi-direction causal linkage among the mentioned variables and discover that tax revenue has significantly positive impacts on economic growth. On the other hand, the effect on growth of economy of the ten institutional quality indices is diverse. The data also indicated convergence in all estimation models as suggested by classical theories of economic growth.